(untitled) (Journal of the Management Sciences, 2025)
This study examined drivers risk attitudes on the demand for insurance claims in Nigeria. Risk attitudes were decomposed into three elements; using cell phone and texting, driving at excessive speed, drinking and driving as independent variables, while insurance claims was the dependent variable. Explanatory research design was adopted in this study. Data was gathered from primary source using structured questionnaires. The sample size for the study was determined using the Taro Yamane formular and multiple regression analysis was used to test the impact of the independent variables on the dependent. Also, to establish the statistical significance of the independent variables, t-statistic at 5% level of significance was used. Coefficient of determination (R2) was also used to establish the predictive power of the independent variables in explaining the variation in the dependent variable. The findings revealed that using cell phone and texting, driving at excessive speed, and drinking and driving had combined significant positive effect with the demand for insurance claims in Nigeria depending on the type of insurance cover possessed by the insured. It was recommended that risk perception training should be implemented to educate drivers about the consequences of risky behaviours such as speeding, drunk driving, and distracting driving, this will help reduce the demand for insurance claims in Nigeria. Also, insurers will have more funds to channel to investments that will enable the insurers attend to claims need whenever it arises.